Reseña de: Joseph Pérez, Cisneros, el cardenal de España, Taurus, 2014, 368 pp. isbn 978-84-306-0948-2 - García Hernán, Enrique (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2016)
Reseña de: Joseph Pérez, Cisneros, el cardenal de España, Taurus, 2014, 368 pp. isbn 978-84-306-0948-2